1997
DOI: 10.1097/00006534-199704000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized Fibular Graft for Reconstruction of the Wrist after Excision of Giant Cell Tumor

Abstract: Seven patients with a giant-cell tumor involving the distal end of the radius were treated with en bloc resection and reconstruction with a free vascularized fibular graft. Two patients with stage 2 disease of Enneking's surgical staging and grade 2 of Campanacci's radiographic grading system were reconstructed with an articular fibular head graft. Five patients with stage 3 and grade 3 disease underwent wrist arthrodesis using fibular shaft transfer. There was radiographic evidence of bone union at the host-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 13 publications
1
58
1
3
Order By: Relevance
“…Sheth et al [36] found comparable MSTS scores and grip strength when comparing intralesional excision and resection arthrodesis, respectively, for giant cell tumor of the distal radius in 26 patients. Some favorable functional results also have been reported for osteoarticular allograft reconstruction using proximal fibular autograft, however none were performed in our patients and there are concerns with high complication rates [1,3,6,23,24,26,31].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Sheth et al [36] found comparable MSTS scores and grip strength when comparing intralesional excision and resection arthrodesis, respectively, for giant cell tumor of the distal radius in 26 patients. Some favorable functional results also have been reported for osteoarticular allograft reconstruction using proximal fibular autograft, however none were performed in our patients and there are concerns with high complication rates [1,3,6,23,24,26,31].…”
Section: Discussionmentioning
confidence: 55%
“…McGough et al [28] reported 30% recurrence in 33 patients, Harness and Mankin [18] reported 42% recurrence in 26 patients, Sheth et al [36] reported 25% recurrence in 12 patients, and O'Donnell et al [30] reported 50% recurrence in 10 patients. Conversely, en bloc resection of the distal radius with either arthrodesis or osteoarticular allograft has reported low recurrence rates of 0% [1,4,5,13,19,31,36,39], with few studies showing recurrence in greater than 25% [26,29].…”
Section: Discussionmentioning
confidence: 99%
“…These differ by the type of graft replacing the resected bone and whether an attempt is made to preserve the radiocarpal articulation. The autogenous grafts described include free vascularized fibula graft [20,25,33,35,38], nonvascularized fibula [6,37,44], vascularized structural iliac crest bone graft (ICBG) [21], nonvascularized ICBG [8], nonvascularized corticocancellous tibial struts [11,46], and use of the ulna adjacent to the involved radius [36,39]. Structural allograft [2,41,45] is a popular alternative in certain countries as well.…”
Section: Introductionmentioning
confidence: 99%
“…Thorough curettage combined with cryosurgery and the packing of bone cement is generally considered the standard treatment for grade I lesions, and can preserve good joint function [8,14]. For grade II or III lesions, or recurrent lesions after curettage, en bloc resection is required because the tumours can only be controlled by wide excision [15,16]. However, large bone defects can result after wide resection of the tumour.…”
Section: Discussionmentioning
confidence: 99%
“…Ono et al [15] suggested that performing wrist arthroplasty with a vascularised fibular head graft is the best surgical approach in the treatment of grade II GCT of the distal radius. Moreover, Saini et al [17] reported a satisfactory clinical outcome after reconstructing bone defects with a non-vascularised proximal fibula graft in 12 cases of GCT of the distal radius after tumour resection.…”
Section: Discussionmentioning
confidence: 99%